Deep inside the virgen forest: the complexity of a mytical element in the Western imaginary about nature (Tempo e Argumento, 2010)
The  virgin forest is a recurrent element in the Brazilian social imaginary.  Although the mistake in considering “virgin” the forested areas has already  been proved, human action, even indirect, left marks throughout the planet.  This essay seeks to understand the reasons for the persistence of the term virgin  forest in our imaginary. It is postulated that the expression “virgin forest”  is part of a modern myth about nature; it is a “misunderstanding” that belongs  to the ethnocentric culture; it is an ideology that justifies the Western  domination; it is an appropriated representation and has been reelaborated in  different social configurations; it is a long-lasting element that is anchored  in the disjunction of nature and culture, which is part of the hegemonic world  view in the West.
Keywords: mith; representation; nature